2017
DOI: 10.1167/iovs.17-21532
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Oxygen Saturation Correlates With Visual Acuity but Does Not Predict Outcome After Anti-VEGF Treatment in Central Retinal Vein Occlusion

Abstract: Citation: Jeppesen SK, Bek T. Retinal oxygen saturation correlates with visual acuity but does not predict outcome after anti-VEGF treatment in central retinal vein occlusion. Invest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
1
17
1
Order By: Relevance
“…The increase in AS is challenging to explain by physiological phenomena, and it could suggest some kind of unknown artificial mechanism in the imaging process since the quality of oximetry images did not differ. Similar increase of AS was observed in studies focusing on retinal vein occlusion where the explanation based on physiology was also difficult (Traustason et al 2014; Jeppesen & Bek 2017; Osaka et al 2019).…”
Section: Discussionsupporting
confidence: 76%
“…The increase in AS is challenging to explain by physiological phenomena, and it could suggest some kind of unknown artificial mechanism in the imaging process since the quality of oximetry images did not differ. Similar increase of AS was observed in studies focusing on retinal vein occlusion where the explanation based on physiology was also difficult (Traustason et al 2014; Jeppesen & Bek 2017; Osaka et al 2019).…”
Section: Discussionsupporting
confidence: 76%
“…It has been reported that retinal oxygen saturation before treatment did not contribute significantly to predicting visual outcome after three‐monthly intravitreal injections with VEGF inhibitor in central retinal vein occlusion (Jeppesen & Bek ). In DME patients, we found there was no significant correlation between VA improvement at 12 months and arterial oxygen saturation before treatment ( r = 0.291, p = 0.119; data not shown), or venous oxygen saturation before treatment ( r = 0.085, p = 0.656; data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…; Blair et al. ), retinal vessel occlusions (Jeppesen & Bek ; Šínová et al. ) and glaucoma (Van Keer et al.…”
Section: Introductionmentioning
confidence: 99%